The Relationship between Self-Esteem and Social Comparison With Body Image of Young People in Makassar City - Nur Aisyah Qatrunnada; Widyastuti .; Perdana Kusuma (Polteknik Ilmu Pemasyarakatan, 2023)
Body image is one of the problems experienced by adolescents during their development. Body image is an evaluation carried out by adolescents on their physical appearance and body shape.. Factors that can influence a teenager's high or low body image are self-esteem and social comparison. This research aims to determine the relationship between self-esteem and social comparison and body image of adolescents in the city of Makassar. There were 311 research respondents who lived in the city of Makassar. The measuring instruments used are the self-esteem scale, social comparison scale and body image scale. Data were analyzed using multiple correlation techniques. The results of the study show that there is a relationship between self-esteem and social comparison on the body image of adolescents in the city of Makassar with a sig value of 0.000<0.05. Based on the R2 value, the results obtained were 0.280, so it can be said that self-esteem and social comparison mutually influence adolescent body image by 28% and 72% are influenced by factors outside the study. The implications of this research are that increasing self-esteem and reducing social comparison can be used as an intervention model to improve adolescent body image.